Anorexia e bulimia: um transtorno alimentar não se trata disso - Tatiana Mattos do Amaral (2007)
The medical and psychiatric concept of Anorexia Nervosa and Bulimia Nervosa are diseases characterized by alimentary disorder and body-image distortion, where compensatory food rejection and/or purgative measures are the central phenomena of the clinical picture. The general and universal aspects of the classification of patients in diagnostic categories, as proposed in DSM-IV and ICD-10, have proven insufficient for the appropriate conduction of the cases. Practical medicaldiagnosis inherently includes the idea of the individual being an instance of a class. The proposal of general criteria classification allows the analysis of global problem data and ensures adequate diagnosis and nomination, but does not contribute to the singularity of each case. A clinic which is closer to the subjective questions of the patients confirms the fact that anorexia and bulimia do not fundamentally constitute an alimentary disorder that is not the case. It is a mistake to approach a case of anorexia and bulimia as an alimentary disorder, no matter how much medical care is demanded by the body repercussions. These clinical phenomena are actually symptomatic expressions in response to psychic conflicts. The universal scientific method excludes subjectivity;but a more accurate listening states that subjectivity prevails. There is yet something that evades a therapeutic and normative proposal. This study proposes, from the construction of clinical cases, that the so-called Alimentary Disorders cannot be reduced to organic illnesses. This understanding, which is built from a psychoanalytical reading, contributes and creates new possibilities to the directions of the treatment. The serial cases do not evade the paradigms admitted in an epistemic community; hence, there are always clinical aspects which can be generalized. The work with each case defines itself as a clinic of the particular. This particularity can only be possible through the way of the singular, by means of a transferential maneuver. The clinical experience the repetition of theoretical aspects in each case, which is determined by the most singular aspects in each patient ensures the transmission of the psychoanalysis knowledge. Particularity then attains a paradigmatic value. The particularity of each case provides it with methodological value and teaches us about treatment directions, in this clinic that urges invention. Psychoanalysis proposes the clinic of one by one, the clinic of the singular. As the universal envelopment of the symptom is unveiled, one can find a particular history the anorexia and bulimia of each subject. Despite the typical phenomenology of the symptoms, each of them is particular and peculiar; the sense of a single symptom is different in each subject. It is about providing individualization from the monotonous and generic series of the anorexic-bulimic phenomena (rituals, vomiting, food restrictions). Through the fragments of clinical cases, we verified that the movement from the clinical picture to the clinical case unveils a series of psychic experiences which point out thesingularity of the subject and reorient the clinic.